Increasing vaccine uptake among employees within the non-health related critical infrastructure sectors: A review. Issue 1 (31st December 2023) - Kalunga, Linda; Bulut, Ece; Chen, Ziqian; Li, Yihong; Ivanek, Renata
ABSTRACT: This review aimed to identify barriers to employee vaccination, motivators for vaccination, and vaccine uptake strategies within the critical infrastructure sectors. We focused on non-healthcare-related sectors, including food and agriculture, manufacturing, and education where employee vaccination is rarely mandated. We conducted a search for literature published from 2012 to 2022 from MEDLINE-PubMed, PsycINFO, and Web of Science Core Collection, which resulted in 22 studies that met the inclusion criteria. We found that 1) barriers to vaccination differ by infectious disease and population; 2) common motivators for vaccination were about protecting self, family, and community; and 3) common uptake strategies for influenza (which accounted for 83% of uptake strategies in reviewed studies) addressed convenience and confidence barriers such as vaccination cost and education. Our review highlights the need for employers, policymakers, and researchers to identify infectious disease and population-specific barriers to vaccination and implement strategies aimed at addressing the identified barriers.